2010
DOI: 10.1186/1475-2875-9-174
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum isolates from Angola show the StctVMNT haplotype in the pfcrt gene

Abstract: BackgroundEffective treatment remains a mainstay of malaria control, but it is unfortunately strongly compromised by drug resistance, particularly in Plasmodium falciparum, the most important human malaria parasite. Although P. falciparum chemoresistance is well recognized all over the world, limited data are available on the distribution and prevalence of pfcrt and pfmdr1 haplotypes that mediate resistance to commonly used drugs and that show distinct geographic differences.MethodsPlasmodium falciparum-infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
66
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 31 publications
4
66
4
1
Order By: Relevance
“…Surprisingly, this haplotype, which is usually found in South America and parts of Asia, was detected in adult samples from Luanda in 2007 (15). Despite the proximity of Luanda to our study site, we have not found this haplotype among our samples, suggesting that AQ would still be effective in this area.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Surprisingly, this haplotype, which is usually found in South America and parts of Asia, was detected in adult samples from Luanda in 2007 (15). Despite the proximity of Luanda to our study site, we have not found this haplotype among our samples, suggesting that AQ would still be effective in this area.…”
Section: Discussioncontrasting
confidence: 66%
“…The different pfcrt mutant haplotypes have a consistent geographical distribution: the CQR haplotype CVIET is predominant in southeast Asia and Africa, whereas the AQ-resistant (AQR) haplotype SagtVMNT is predominant in Asia and South America, and StctVMNT, from South America, is very rare in Africa (16).The wild-type haplotype CVMNK is widespread (6,16,29,38). A recent study reported the presence of the StctVMNT haplotype of pfcrt in Angola, but this has not yet been verified by others (15,37). Polymorphisms in the parasite protein Pgh-1, encoded by pfmdr1, are thought to modulate resistance to drugs such as quinine, mefloquine, halofantrine, artemisinin, lumefantrine, CQ, and AQ (1,21,32,38).…”
mentioning
confidence: 99%
“…8,21,22 Our single nucleotide polymorphisms findings in isolates from Brazil and Nigeria provide additional evidence supporting the association of SVMNT and CVIET haplotypes respectively with P. falciparum isolates of South American and African origin. However, recent studies from Africa, notably in Tanzania, 3 Angola, 17 and Ghana 22 have reported the presence of SVMNT pfcrt haplotype in parasites from these various areas. Although it has been proposed that human migration and the strong commercial relationship between Brazil and Angola could have allowed for the import of the SVMNT haplotype from Brazil to Angola, 17 the same haplotype was found in parasites from Tanzania, 3 a country without strong commercial relationship with South America.…”
mentioning
confidence: 98%
“…However, recent studies from Africa, notably in Tanzania, 3 Angola, 17 and Ghana 22 have reported the presence of SVMNT pfcrt haplotype in parasites from these various areas. Although it has been proposed that human migration and the strong commercial relationship between Brazil and Angola could have allowed for the import of the SVMNT haplotype from Brazil to Angola, 17 the same haplotype was found in parasites from Tanzania, 3 a country without strong commercial relationship with South America. AQ has been suggested, as the driver of the selection of the SVMNT haplotype in Tanzania.…”
mentioning
confidence: 98%
See 1 more Smart Citation